MANAGEMENT OF PATIENTS WITH PURULENT MEDIASTINITIS IN THE POSTOPERATIVE PERIOD - Okhunov, A.O.; Abdullaev, Sh.Yu.; Boboyev, K.Kh.; Babokhujaev, A.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
In this review article, we presented modern data on the treatment of patients with purulent mediastinitis in the postoperative period. Purulent mediastinitis remains an extremely severe and life-threatening form of acute surgical pathology, the prevalence of which has remained stable for many years with a moderately pronounced tendency to increase. The main cause of adverse outcomes in patients with purulent mediastinitis is the untimely performance of surgical interventions, due in turn to diagnostic errors at all stages of medical care. Use of proposed standards Examination of patients with suspected purulent inflammation of the mediastinal tissue in typical clinical situations can reduce the time for diagnosing purulent mediastinitis. The use of a system for monitoring the course of the postoperative period in patients with purulent mediastinitis makes it possible to ensure early detection of postoperative complications in case of occurrence. The implementation of the principles of organizing the provision of medical care to patients with purulent mediastinitis makes it possible to increase the frequency of referral to a specialized hospital for patients with suspected purulent mediastinitis and, as a result, increase the frequency of early diagnosis of this disease.